Transformation of Sharia Economy in The Digital Era: A Conceptual Analysis of The Integration of Sharia Fintech, Maqāṣid Al-Sharī'ah, And The Financial Inclusion of The Ummah - Doni Abdul Rohman; Mukhsin Irfangi; Muhammad Hanif Abdillah (Kirana Publisher (KNPub), 2026)
The transformation of the digital economy has encouraged the acceleration of the development of financial technology (fintech) in various countries, including in the sharia economic ecosystem. In Indonesia, the growth of sharia fintech shows a positive trend in line with the increasing need for financial services that are inclusive, transparent, and in accordance with sharia principles. However, the integration between financial technology innovation and the normative framework of maqāṣid al-sharī'ah still requires conceptual strengthening so that it is not just a technical adaptation of the conventional system. This research aims to analyze the conceptual construction of sharia fintech from an Islamic economic perspective, explore the integration of maqāṣid al-sharī'ah in its business model, and examine its contribution to increasing the financial inclusion of the ummah. The research uses a qualitative approach with the library research method through thematic analysis of academic literature, financial authority reports, and related regulations and fatwas. The results of the study show that sharia fintech has significant potential in expanding access to financing for the unbanked and MSMEs, increasing transaction efficiency, and strengthening transparency in fund management based on the principles of ḥifẓ al-māl and consumer protection. However, the main challenge lies in the aspects of digital literacy, regulatory harmonization, and consistency in the application of sharia principles in operational practices. This research emphasizes that the integration of sharia fintech based on maqāṣid al-sharī'ah is not only an instrument of technological innovation, but also a financial system transformation strategy oriented towards distributive justice and the welfare of the ummah in a sustainable manner.